2016
DOI: 10.5935/1806-6690.20160066
|View full text |Cite
|
Sign up to set email alerts
|

Non-hierarchical clustering ofManihot esculentaCrantz germplasm based on quantitative traits

Abstract: -The knowledge of the phenotypic variation of cassava (Manihot esculenta Crantz) germplasm allows the estimative of the genetic variability to support the selection of contrasting genitors. Therefore, the aim of this work was to define homogeneous groups of cassava germplasm based on yield traits, disease resistance and root quality using K-means as a nonhierarchical method. Breeding values estimated by Best Linear Unbiased Predictor (BLUP) were used for the cluster analysis. The number of groups was defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…FCB Araújo et al 'Bitter' cassava had higher starch and sugar contents than the group of 'sweet' cassava ( Table 3). The starch contents were similar to those identified in another study with cassava accessions sampled in Brazil (Vieira et al 2015, Oliveira et al 2016.…”
Section: Resultssupporting
confidence: 84%
“…FCB Araújo et al 'Bitter' cassava had higher starch and sugar contents than the group of 'sweet' cassava ( Table 3). The starch contents were similar to those identified in another study with cassava accessions sampled in Brazil (Vieira et al 2015, Oliveira et al 2016.…”
Section: Resultssupporting
confidence: 84%
“…Cluster analysis, specifically K-means clustering, can be used to group cultivars based on multiple metrics. For example, Oliveira et al (2016) used the K-means algorithm to cluster accessions of a large cassava (Manihot esculenta) germplasm set into distinct groups based on several yield, disease resistance and root traits. They were able to identify groups of promising cultivars for production and/or for use as breeding parents.…”
Section: Discussionmentioning
confidence: 99%
“…According to Oliveira et al (2016), some cassava genotypes showed differential resistance to Fusarium spp., Phytophthora spp. and the Botryosphaeriaceae species in the peel and pulp.…”
Section: Discussionmentioning
confidence: 99%